Assessing Sustainability over Space and Time: The Emerging Roles of GIScience and Remote Sensing - Estoque, Ronald (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Sustainability is a critical global challenge that requires comprehensive assessments of environmental, social, and economic indicators. The formulation of the 17 Sustainable Development Goals (SDGs) represents a significant leap forward in humanity's pursuit of sustainability. The SDGs now serve as a shared platform for global development, guiding current actions towards and shaping visions of a sustainable future. Monitoring progress towards the SDGs and sustainability in general is essential. This is true not only at the global and national scales, but also at the subnational and landscape levels. Geographic information science (GIScience) and remote sensing (RS) have made significant advances in these areas. These breakthroughs include the increasing availability of geospatial data, a development which plays a crucial role in this regard. This Special Issue aimed to bring together novel contributions on the assessment of sustainability and sustainability-related indicators over space and time using geospatial data, tools, and techniques (GIScience and RS). This publication contains 11 peer-reviewed papers, including two review articles and nine research articles.